2015
DOI: 10.17957/ijab/14.0030
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tillage, Nitrogen and Stubble Management on Phenology and Crop Establishment of Wheat

Abstract: To cite this paper: Basir, A., M.T. Jan, M. Arif and M.J. Khan, 2016 ) application. The objective of the study was to examine the treatment effects on phenology, establishment and yield of succeeding wheat crop. Result showed that wheat phenology except days to emergence was not affected by different TS however; early emergence (10 days) was observed in minimum tillage rather than conventional and deep tillage system. Nitrogen fertilization (120 kg N ha -1 ) enhanced days to phenological observations, while no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…This is may be due to increase soil aeration and increase proliferation of roots for uptake of more nutrients by the plant in deep tillage systems, this lead to increase the duration of vegetative growth. Our results was in agreement with results of other researchers Malagi (2010) and Basir et al (2016), which they are reported that tillage systems had a significant effect in the number of days until tasseling.…”
Section: Number Of Days Until 50% Tasselingsupporting
confidence: 94%
“…This is may be due to increase soil aeration and increase proliferation of roots for uptake of more nutrients by the plant in deep tillage systems, this lead to increase the duration of vegetative growth. Our results was in agreement with results of other researchers Malagi (2010) and Basir et al (2016), which they are reported that tillage systems had a significant effect in the number of days until tasseling.…”
Section: Number Of Days Until 50% Tasselingsupporting
confidence: 94%
“…It was also documented by Badaruddin et al (1999), that plants have more tiller potential when received the N from both inorganic as well as organic source compared to either source. Basir et al (2016) also confirmed that reduced tillage and plots having organic matter incorporated produced maximum number of tillers m -2 as compared with deep tillage and control plots.…”
Section: Tiller M -2supporting
confidence: 64%
“…This might be due the reason that integration of tillage practices and incorporation of nitrogen fertilizers in both organic and inorganic form improved soil water holding capacity (Al-Kaisi and Yan, 2005) and SOC (Dolan et al, 2006). These results are supported by Khan et al (2009) and were confirmed by Basir et al (2016).…”
Section: Days To Emergence and Emergence M -2mentioning
confidence: 66%
“…The minimal soil disturbance that reduces soil water loss through lower evaporation may account for faster growth in zero tillage systems. The softened seedbed helped in rapid emergence (Basir et al, 2011;Edalat and Naderi, 2016). The short-duration lentil variety L4717 recorded the minimum number of days in each of the growth stages noted (days to flower initiation, 42.8 and 43.6 days, flowering to pod initiation, 20.0 and 20.5 days, pod initiation to maturity, 38.7 and 38.8 days) in both years as compared to the long-duration variety Moitri (Table 3) due to their faster growth habit and good climate advantages.…”
Section: Impact On Phenology and Gddmentioning
confidence: 99%